Treatment of Bronchopleural and Alveolopleural Fistulas in Acute Respiratory Distress Syndrome With Extracorporeal Membrane Oxygenation, a Case Series and Literature Review. (14th May 2021) - Odish, Mazen F.; Yang, Jenny; Cheng, George; Yi, Cassia; Golts, Eugene; Madani, Michael; Pollema, Travis; Owens, Robert L.
Abstract : OBJECTIVES: To describe a ventilator and extracorporeal membrane oxygenation management strategy for patients with acute respiratory distress syndrome complicated by bronchopleural and alveolopleural fistula with air leaks. DESIGN, SETTING, AND PARTICIPANTS: Case series from 2019 to 2020. Single tertiary referral center—University of California, San Diego. Four patients with various etiologies of acute respiratory distress syndrome, including influenza, methicillin-resistant Staphylococcus aureus pneumonia, e-cigarette or vaping product use-associated lung injury, and coronavirus disease 2019, complicated by bronchopleural and alveolopleural fistula and chest tubes with air leaks. MEASUREMENTS AND MAIN RESULTS: Bronchopleural and alveolopleural fistula closure and survival to discharge. All four patients were placed on extracorporeal membrane oxygenation with ventilator settings even lower than Extracorporeal Life Support Organization guideline recommended ultraprotective lung ventilation. The patients bronchopleural and alveolopleural fistulas closed during extracorporeal membrane oxygenation and minimal ventilatory support. All four patients survived to discharge. CONCLUSIONS: In patients with acute respiratory distress syndrome and bronchopleural and alveolopleural fistula with persistent air leaks, the use of extracorporeal membrane oxygenation to allow for even lower ventilator settings than ultraprotective lung ventilation is safe and feasible to mediate bronchopleural and alveolopleural fistula healing.